Digital Literacy among Teachers – Mapping Theoretical Frameworks: TPACK, DigCompEdu, UNESCO, NETS-T, DigiLit Leicester - Lukasz TOMCZYK; Laura FEDELI (Communications of International Proceedings, 2021)
The aim of this article is to systematically review the most influential and widely discussed theoretical frameworks that relate to the digital literacy (DL) of teachers. The aim of the research is to show the differences and similarities between the most popular theoretical frameworks on DL. The choice of theoretical frameworks was dictated by the visibility (citability) of the different concepts. The research review includes the five most frequently cited concepts for understanding the phenomenon of the implementation of ICT in education at different levels of formal and university education. The article synthesizes and compares such concepts as TPACK, DigCompEdu, UNESCO, NETS-T, and DigiLit Leicester. Based on the analyses, it was noted that: 1) There is no one-size-fits-all way to measure DL among teachers; 2) The aforementioned theoretical frameworks mostly have clearly defined areas and levels of DL; 3) Most of the concepts assume measurement through self-declaration, abandoning measurement through practical activities; 4) All concepts clearly emphasize that DL cannot be separated from teaching processes; 5) DL among teachers differs from DL among other professional groups, this being due to the specifics of the field; 6) Differences in the formation of the most popular theoretical frameworks may be due to the richness of definitions of DL and the diversity of views on the process of the computerization of education; 7) A common feature of the analyzed frameworks is the integration of DL with methodological elements (content, methods, forms), and teacher and learner development; and 8) The selected frameworks possess their own measurement tools.
Keywords: Digital literacy; Digital competence; teachers; theoretical framework.